Humanistic medicine in anaesthesiology: development and assessment of a curriculum in humanism for postgraduate anaesthesiology trainees - Canales, Cecilia; Strom, Suzanne; Anderson, Cynthia T.; Fortier, Michelle A.; Cannesson, Maxime; Rinehart, Joseph B.; Kain, Zeev N.; Perret, Danielle (British journal of anaesthesia : BJA, 2019)
An unintended consequence of medical technologies is loss of personal interactions and humanism between patients and their healthcare providers, leading to depersonalisation of medicine. As humanism is not integrated as part of formal postgraduate anaesthesiology education curricula, our goal was to design, introduce, and evaluate a comprehensive humanism curriculum into anaesthesiology training. Subject-matter experts developed and delivered the humanism curriculum, which included interactive workshops, simulation sessions, formal feedback, and patient immersion experience. The effectiveness of the programme was evaluated using pre- and post-curriculum assessments in first-year postgraduate trainee doctors (residents). The anaesthesiology residents reported high satisfaction scores. Pre-/post-Jefferson Scale of Patient Perceptions of Physician Empathy showed an increase in empathy ratings with a median improvement of 12 points (range; P=0.013). After training, patients rated the residents as more empathetic (31 [4] vs 22 [5]; P<0.001; 95% confidence interval [CI]: 7–12) and professional (47 [3] vs 35 [8]; P<0.001; 95% CI: 9–16). Patient overall satisfaction with their anaesthesia provider improved after training (51 [6] vs 37 [10]; P<0.001; 95% CI: 10–18). Patients rated their anxiety lower in the post-training period compared with pretraining (1.8 [2.3] vs 3.6 [1.6]; P=0.001; 95% CI: 0.8–2.9). Patient-reported pain scores decreased after training (2.3 [2.5] vs 3.8 [2.1]; P=0.010; 95% CI: 0.4–2.8). Implementation of a humanism curriculum during postgraduate anaesthesiology training was well accepted, and can result in increased physician empathy and professionalism. This may improve patient pain, anxiety, and overall satisfaction with perioperative care.